Effects of interruption on eye movements and comprehension during reading on digital devices. (August 2022) - Chevet, Guillaume; Baccino, Thierry; Marlot, Lucas; Vinter, Annie; Drai-Zerbib, Véronique
Abstract: The growing use of digital devices brings about interruptions during reading. The aim of the present study is to observe the consequences of an interruption on reading behavior and text comprehension when the information that is evaluated is the information that is being read at the time the interruption occurs. Eye movements (mean number of fixations, regressive fixations and mean fixation duration) were recorded while reading four long texts. Reading was interrupted by an arithmetic verification task either in the middle of a paragraph (intra-paragraph condition) or between two successive paragraphs (inter-paragraph condition). The analysis of the eye movements showed more rereading behaviors when an interruption occurred. The participants who understood the text best were also those who reread the most. The comprehension performances were not affected by the interruption, irrespective of its position (inter- or intra-paragraph). This preservation of performance is discussed in relation to LTWM theory. Highlights: Rereading behaviors following an interruption. The comprehension of locally interrupted information is not disturbed. The participants who reread are more successful in comprehending the text. Auditory-verbal memory span predicts interrupted reading comprehension performance.